Multicystic Dysplastic Kidney: A Case Report - Ingar-Pinedo, Jaime (2019)
Multicystic renal dysplasia is a rare and little know in our country. The aim of this paper is to present and critically discuss the diagnosis, assessment and perinatal outcome of a case of multicystic dysplastic kidney and its differential diagnosis.